Quatro décadas de mobilidade social no Brasil - Carlos Antonio Costa Ribeiro (Universidade do Estado do Rio de Janeiro, 2012)
This article analyzes intergenerational class mobility and inequality of opportunities over the last 40 years in Brazil. We draw on five national sample surveys conducted from 1973 to 2008 in order to examine the mechanisms that led to changes in social fluidity (inequality of opportunities) for men and women. The analyses show that there was a substantial decrease in inequality of opportunities (increase in social fluidity). The decrease in inequality of opportunities in Brazil relates to two mechanisms: a reduction in educational returns during this period, and a decrease in the direct effect of class of origin on class destination, discounting the effect of educational attainment, until 1988 for men and until 1996 for women. Beginning in these two years, we detect an increase in the direct effect of class of origin on class destination, controlling for education. We also discuss the principal consequences of the study's findings for the analysis of social inequalities in Brazil.